The Role of Housing in the Spatial Distribution of Unemployment in Poland - Maciej Tarkowski (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Labour market and housing problems are an important part of social studies, though spatial analysis of labour market diversification and housing resources are not the dominating subject of studies. The interaction between the place of residence and the place of work is treated in terms of commuting to work, but this aspect does not exhaust the issue. The article is an attempt to answer the question whether a relation exists between the structure of housing and its accessibility and the stable diversification of local labour markets. A necessary condition for permanent migration from a location that does not offer work to that characterised by labour demand, is the accessibility of housing offering acceptable living conditions. The decades‑lasting housing deficit and the efforts to improve the situation relying solely on market mechanisms seem to restrict housing accessibility considerably. To answer this question a model of spatial regressions was construed, based on statistical data aggregated at the district (county) level. The results indicate a considerable role of financial accessibility of housing, in terms of purchase capacity and remuneration in particular districts, in preserving the disparities among local labour markets.